The Entrepreneurial Scholar - Dimov, Dimo (Edward Elgar Publishing, 2020)
Dimo Dimov's innovative book examines what it means to be an entrepreneurial scholar, drawing on a range of philosophical ideas to investigate the study of entrepreneurs. Dimov makes the case for entrepreneurial scholarship to become more future-oriented and creates a framework, highlighting four styles and approaches to the field: theoretical, integrative, craft and clinical. This thought-provoking book will be a stimulating read for academics and students of entrepreneurship, and its accessible format will also appeal to reflective practitioners.